The Qur’anic Concept of Teachers and Its Educational Principles in Contemporary Educational Contexts - Abu Warasy Batula; Cucu Surahman; Elan Sumarna; Puput Rahmania; Intan Wardatul Karimah (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2025)
This study aims to systematically reconstruct the Qur’anic concept of teachers and to identify its foundational educational principles, while critically examining their relevance within contemporary educational contexts marked by digital transformation, moral fragmentation, and technocratic tendencies. Employing a qualitative library-based research design, this study utilizes the thematic Qur’anic interpretation (tafsir maudhu‘i) method integrated with a tarbawi interpretative perspective. Primary data were derived from selected Qur’anic verses addressing teacher identity, ethical responsibility, and pedagogical interaction, while secondary data included classical and contemporary tafsir as well as recent scholarly works in Islamic education and modern pedagogy. The findings reveal that the Qur’an conceptualizes teachers as bearers of wisdom (ḥikmah), compassionate guides, and moral-spiritual exemplars whose personal integrity constitutes an integral dimension of pedagogy. Core principles identified include tawḥīd as the ontological foundation of education, the integration of knowledge and ethical discernment, compassion-based leadership, deliberative and participatory learning (shūrā), character formation (tarbiyah akhlāqiyah), and reliance upon God (tawakkul). The novelty of this study lies in its integrative methodological framework that directly reconstructs teacher identity from Qur’anic discourse and systematically contextualizes it within contemporary global educational challenges. This study contributes both theoretically, by advancing a Qur’an-based educational paradigm, and practically, by offering a holistic, ethically grounded framework for strengthening teacher professionalism, character education, and spiritually oriented pedagogy in modern educational institutions.